Tuberculine reaction measured by infrared thermography. Issue 2 (November 2015) - Fiz, José Antonio; Lozano, Manuel; Monte-Moreno, Enrique; Gonzalez-Martinez, Adela; Faundez-Zanuy, Marcos; Becker, Caroline; Pons-Rodriguez, Laura; Ruiz Manzano, Juan
Highlights First paper devoted to tuberculine reaction measurement based on thermal imaging. There is good agreement in area length of tuberculin reaction between visual and thermographic evaluation. Automatic generation of positive and negative results of the tuberculin skin test evaluated by infrared imaging.